Detection of gene mutation in a case of Nagashima-type palmoplantar keratoderma - CAO Yuanyuan; YUAN Zhaojun; JIN Chuanyang; WANG Tianzi; LIAO Xiaojie; LIU Hong (Pifu-xingbing zhenliaoxue zazhi)
[Objective] To report a case of Nagashima-type palmoplantar keratoderma (NPPK), identify pathogenic gene, and assist clinical diagnosis and classification of this disease. [Methods] Clinical data of the patient were collected. Genomic DNA was extracted from the patient′s peripheral blood sample. Whole exome high-throughput sequencing was used to identify the pathogenic mutation, and Sanger sequencing was applied to verify the mutation site. [Results] Heterozygous mutations of c.455G>T (p.Gly152Val) and c.796C>T (p.Arg266Ter) were found in the patient. The patient′s father was a heterozygous carrier of the mutation c.455G>T without the c.796C>T mutation, and his mother was a heterozygous carrier of the mutation c.796C>T without the c.455G>T mutation. Together with the clinical manifestations of diffuse erythema on the palms and toes since childhood, the patient was diagnosed with NPPK. [Conclusions] The c.455G>T and c.796C>T heterozygous mutations in the SERPINB7 gene are the pathogenic cause of NPPK in this patient. The diagnosis and disease type of the patient are clarified, and genetic counseling is provided according to the patient′s request.